2020
DOI: 10.3164/jcbn.19-90
|View full text |Cite|
|
Sign up to set email alerts
|

The association among enterobacterial flora, dietary factors, and prognosis in patients with ulcerative colitis

Abstract: The role of enterobacterial flora in the onset and progression of inflammatory bowel diseases is a topic of considerable interest. Here, we assessed the association among enterobacterial flora, dietary factors, and ulcerative colitis (UC) progression. Forty six patients with UC who were diagnosed as being in remission were enrolled. We collected each patient's stool sample one or two days before diagnostic colonoscopy. After colonoscopy, we observed the patients for one year and then retrospectively divided th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…(1) Although there is increasing evidence showing associations with genetic, immune system, and environmental factors, as well as possible microbiota involvement in the pathogenesis of UC, those details remain unclear. (2)(3)(4) Nevertheless, several pharmacological agents proven to provide benefits for the condition have been developed, with 5aminosalicylic acid (5-ASA) the first choice for those with mild to moderate UC. (5) Should that fail, treatment with corticosteroids (CS) is usually then initiated.…”
mentioning
confidence: 99%
“…(1) Although there is increasing evidence showing associations with genetic, immune system, and environmental factors, as well as possible microbiota involvement in the pathogenesis of UC, those details remain unclear. (2)(3)(4) Nevertheless, several pharmacological agents proven to provide benefits for the condition have been developed, with 5aminosalicylic acid (5-ASA) the first choice for those with mild to moderate UC. (5) Should that fail, treatment with corticosteroids (CS) is usually then initiated.…”
mentioning
confidence: 99%
“…(14) Recent studies have suggested an association of autophagy and ER stress in the pathophysiology of IBD. (15)(16)(17) For example, enhanced ER stress is observed in the Paneth cells of CD patients with SNP of the ATG16L1 gene. (18) The double knockout mice of ATG16L1 and XBP-1 develop spontaneous enterocolitis that resembles human IBD.…”
mentioning
confidence: 99%